2023
DOI: 10.5195/ie.2023.288
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating the EdD and the PhD in Higher Education

Abstract: Purpose: Higher education, as a field of study, is one of the few programmatic areas that offer two doctoral degrees: The Doctor of Education (EdD) and the Doctor of Philosophy (PhD). In the United States, the two degrees are often conflated. Conversations, to this point, have done more to contribute to the theoretical debate than to operationally distinguish between the two degree paths. Method: The current study analyzed data collected from a review of the 188 doctoral programs at 145 institutions listed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…We argue that these two types of positionalities were prevalent in DiPs due to the focus of our program on action research as a signature pedagogy (Buss, 2018;Zambo, 2011), and the requirement for our students to conduct research within their professional setting and scope of influence (Arslan- Ari et al, 2018). These findings align with previous reports of practitioner programs when privileging action research (Foster et al, 2023;Vaughan & Burnaford, 2015). Consequently, very few students positioned themselves as outsiders who studied or who collaborated with insiders.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…We argue that these two types of positionalities were prevalent in DiPs due to the focus of our program on action research as a signature pedagogy (Buss, 2018;Zambo, 2011), and the requirement for our students to conduct research within their professional setting and scope of influence (Arslan- Ari et al, 2018). These findings align with previous reports of practitioner programs when privileging action research (Foster et al, 2023;Vaughan & Burnaford, 2015). Consequently, very few students positioned themselves as outsiders who studied or who collaborated with insiders.…”
Section: Discussionsupporting
confidence: 79%
“…To date, action research has been widely adopted in online and on-ground EdD programs as a signature pedagogy and research methodology (Foster et al, 2023;Vaughan & Burnaford, 2015). In many EdD programs, action research requires access to a professional setting, allowing practitioners to systematically investigate a problem in their contexts (Buss, 2018;Firestone et al, 2021).…”
Section: Action Researchmentioning
confidence: 99%
“…The job-embedded inquiry expected of educational leaders in EdD programs is distinct from the analytical and theoretical inquiry orientation of traditional students in doctor of philosophy (PhD) programs, yet universities and IRB offices expect both groups of students to engage in research in identical ways during their doctoral preparation and to be held to the same IRB regulations. This expectation may be the case because, as Foster et al (2023) showed, there are many similarities between what is required for a PhD and EdD when it comes to admission requirements and research work.…”
Section: Vignette #2: Principal Jonesmentioning
confidence: 99%
“…Despite these challenges, recent research indicates that the field may be shifting towards more practitioner-oriented research methods preparation. For example, in a study looking for differences between required research methods courses and research credit hours in the PhD and EdD, Foster et al (2023) found that PhD programs required significantly more research hours than EdD programs. The difference was greater at institutions that offered both degrees, which suggests those institutions are working to differentiate the degrees.…”
Section: A Changing Tide?mentioning
confidence: 99%
“…Despite the transformative and rapid progress that EdD reformers and CPED member institutions have made toward reenvisioning the EdD (Bengston et al, 2016;Foster et al, 2023;Perry et al, 2015), debates remain as to how the EdD is distinct from the PhD (See Foster et al (2023) for a more complete discussion.). Intertwined in these debates, and a key component of them, is the role of research methods (Hochbein & Perry, 2013).…”
Section: Introductionmentioning
confidence: 99%